1992
DOI: 10.1148/radiology.184.3.1509084
|View full text |Cite
|
Sign up to set email alerts
|

Wallstent metallic biliary endoprosthesis: MR imaging characteristics.

Abstract: Image quality and safety of magnetic resonance (MR) imaging were evaluated in vitro and in eight patients with the most commonly employed metallic biliary endoprosthesis. In vitro, the stent produced no tip deflection at 0.6 or 1.5 T. Trace magnetic susceptibility artifact, similar to artifact from a column of air, paralleled the stent. In patients, image degradation was minimal with conventional pulse sequences. Middle-field-strength spin-echo images revealed minimal artifacts indistinguishable from those pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

1997
1997
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…The artifact formation is, however, not large enough to compromise the evaluation of the stent surroundings (i.e., the portal region and the pancreatic head). This confirms the findings of Girard et al [18] who performed MR imaging using mid-field systems in eight patients with indwelling biliary Wallstents and reported that visualization of adjacent structures was not influenced by any significant artifact overlay when spin-echo sequences were used. The signal of the interior lumen of the Easy Wallstent is, however, totally obliterated; hence, no evaluation with regard to sludge incrustation or tumor infiltration is possible using this stent system.…”
Section: Asupporting
confidence: 90%
“…The artifact formation is, however, not large enough to compromise the evaluation of the stent surroundings (i.e., the portal region and the pancreatic head). This confirms the findings of Girard et al [18] who performed MR imaging using mid-field systems in eight patients with indwelling biliary Wallstents and reported that visualization of adjacent structures was not influenced by any significant artifact overlay when spin-echo sequences were used. The signal of the interior lumen of the Easy Wallstent is, however, totally obliterated; hence, no evaluation with regard to sludge incrustation or tumor infiltration is possible using this stent system.…”
Section: Asupporting
confidence: 90%
“…Many different types of intravascular and intracavitary coils and stents have been evaluated for safety with MR systems at 1.5-T or less (6,14,18,19,(37)(38)(39)(40)(41)(42). Additionally, a GDC tested at 3.0-T was reported to be safe for this environment (21).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is unlikely that they would become moved or dislodged as a result of being attracted by static magnetic fields of MR systems up to 1.5-T (6,14,18,19,(37)(38)(39)(40)(41)(42). Furthermore, there has never been a report of such an incident.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Many types of guide wires and catheters have been investigated in ultrafast MR imaging. 19 Although we found several articles about MRA of vascular stents, [20][21][22][23][24] reports evaluating the Simon nitinolˆlter with non-contrast MRA are limited.…”
Section: Discussionmentioning
confidence: 99%
“…7,17 The Gianturco stent, made of 304 stainless steel, was reported to create a large``black hole'' artifact in T1-weighted spin-echo MR images ex vivo. 18 Clearly, 316L stainless steel is the preferred material with respect to ferromagnetic properties. 17 Johnson et al carried out MR imaging follow-up of 16 patients with the stainless Greeneldˆlter.…”
Section: Discussionmentioning
confidence: 99%